2018
DOI: 10.1101/480426
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effect of plasma lipids and lipid lowering interventions on bone mineral density: a Mendelian randomization study

Abstract: Statin treatment increases bone mineral density (BMD) and reduces fracture risk, but the underlying mechanism is unclear. We used Mendelian randomization (MR) to assess whether this relation is explained by a specific effect in response to statin use, or by a general effect of lipid-lowering. We utilized 400 single nucleotide polymorphisms (SNPs) robustly associated with plasma lipid levels and results from a heel BMD GWAS (derived from quantitative ultrasound) in 426,824 individuals from the UK Biobank. We pe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
(79 reference statements)
0
4
0
Order By: Relevance
“…For example, Kemp et al used a one-sample multivariable method to show that BMI SNPs acted via both lean and fat mass to increase BMD (34). In an MR analysis of relationships between plasma lipids and BMD, we observed a strong inverse association between LDL cholesterol and forearm BMD in multivariate MR analyses adjusting for HDL cholesterol and triglycerides, which was not evident in univariate analyses involving only LDL cholesterol (59). This indicates that complex relationships may exist between the causal effects of different lipids and BMD, which MR analyses need to account for, and may help to explain the conflicting results from different MR analyses examining relationships between lipid levels and eBMD in the UK Biobank (53, 59, 60).…”
Section: Addressing Pleiotropymentioning
confidence: 70%
See 1 more Smart Citation
“…For example, Kemp et al used a one-sample multivariable method to show that BMI SNPs acted via both lean and fat mass to increase BMD (34). In an MR analysis of relationships between plasma lipids and BMD, we observed a strong inverse association between LDL cholesterol and forearm BMD in multivariate MR analyses adjusting for HDL cholesterol and triglycerides, which was not evident in univariate analyses involving only LDL cholesterol (59). This indicates that complex relationships may exist between the causal effects of different lipids and BMD, which MR analyses need to account for, and may help to explain the conflicting results from different MR analyses examining relationships between lipid levels and eBMD in the UK Biobank (53, 59, 60).…”
Section: Addressing Pleiotropymentioning
confidence: 70%
“…This analysis suggested that 394 of 404 SNPs exerted their primary effect on BMD as opposed to LDL-C levels. IVW MR, weighted median MR and MR-Egger regression results showed some evidence that eBMD might influence LDL-C, and the association remained unchanged after Steiger filtering to remove those SNPs that primary affected LDL-C levels (59).…”
Section: Distinguishing Genetic Correlation From Causalitymentioning
confidence: 99%
“…Trait Cases Controls Total Proportion of cases r 2 = 0.01 r 2 = 0.02 r 2 = 0.03 r 2 = 0.04 r 2 = 0.05 25 variance is explained by the genetic variants used in the current study.…”
Section: Outcome Minimum Detectable Odds Ratiomentioning
confidence: 84%
“…When selecting SNPs from the GWAS, especially in very large GWAS, it can be difficult to determine whether a SNP has its primary association with the exposure being studied or the outcome [25]. For and outcome (COVID-19 phenotypes).…”
Section: Introductionmentioning
confidence: 99%